Activity of β-galactosidase and α-mannosidase in the serum of patients with colon adenocarcinoma - Szajda, Sławomir Dariusz; Snarska, Jadwiga; Borzym-Kluczyk, Małgorzata; Zalewska, Beata; Waszkiewicz, Napoleon; Bierć, Marcin; Zwierz, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2007)
Exoglycosidases β-galactosidase (GAL) and α-mannosidase (MAN) take part in the synthesis of glycoconjugates in the endoplasmatic reticulum and Golgi apparatus, as well as their degradation in the lysosomes. An increase in the activity of exoglycosidases has been reported in the tissues and body fluids of patients with cancer. The aim of our study was to evaluate the activity of GAL and MAN in the serum of patients with colon adenocarcinoma. The serum samples were taken from 14 patients with colon adenocarcinoma (confirmed histopathogically) and from 14 healthy persons.GAL and MAN were determined in the blood serum by Zwierz et al., method as modified by Szajda et al. on the microplate reader (EL X 800 of BIO-TEK). The concentration of GAL and MAN activity was expressed in pKat/ml and the specific activity in pKat/mg of protein. The concentration of protein in the blood serum was determined by the method of Lowry et al. and expressed in mg/ml.We showed significantly increased concentration of GAL (p=0.002) and MAN (p=0.02) activities in the blood serum of patients with colon adenocarcinoma, in comparison to serum GAL and MAN activities of healthy persons. No significant differences (p=0.9511) were found in the concentration of protein in blood serum of patients with colon adenocarcinoma, in comparison to healthy persons. There were significantly higher specific activities of GAL (p=0.003) and MAN (p=0.03) in blood serum of colon adenocarcinoma patients, in comparison to GAL and MAN activities in blood serum of healthy persons.Significantly increased activities of GAL and MAN in blood serum of patients with colon adenocarcinoma suggest the possibility of determination of GAL and MAN serum activity as markers of colon adenocarcinoma. However, further studies are necessary to confirm the diagnostic value for the determination of serum activity of GAL and MAN in oncological diagnostics of colon adenocarcinoma.